1977
DOI: 10.1093/ajcp/67.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Lung Biopsy inPneumocystis cariniiPneumonia: A Histopathologic Study of Typical and Atypical Features

Abstract: This study of 36 patients with Pneumocystis carinii pneumonia emphasizes a spectrum of histopathologic changes that have not been classically considered features of the infection. These atypical microscopic findings were present in 69% of the cases as defined in this retrospective examination. As expected, the suggestion of the correct diagnosis of Pneumocystis carinii pneumonia on the basis of a frozen section and without the aid of appropriate special stains was extremely difficult in the majority of biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…On the other hand, it is conceivable that, owing to the peculiar pathogenetic pathways of AIDS-related PCP, inflection points never occur in the static inflation V-P curve of these patients. In fact, the pathological findings of PCP in AIDS patients include interstitial infiltrates associated with alveolar occupation by eosinophilic exudates, hyaline membranes, macrophages, and cellular debris, which oppose recruitment, whilst oedema is moderate or absent [8,9]. Moreover, computed tomography scan performed in eight of our patients exhibited homogeneous diffuse interstitial and alveolar infiltration, at variance with what appears to be the most common finding in ARDS patients in whom dense opacities are mainly confined to the dependent lung regions [27].…”
Section: Static Inflation V-p Curvementioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it is conceivable that, owing to the peculiar pathogenetic pathways of AIDS-related PCP, inflection points never occur in the static inflation V-P curve of these patients. In fact, the pathological findings of PCP in AIDS patients include interstitial infiltrates associated with alveolar occupation by eosinophilic exudates, hyaline membranes, macrophages, and cellular debris, which oppose recruitment, whilst oedema is moderate or absent [8,9]. Moreover, computed tomography scan performed in eight of our patients exhibited homogeneous diffuse interstitial and alveolar infiltration, at variance with what appears to be the most common finding in ARDS patients in whom dense opacities are mainly confined to the dependent lung regions [27].…”
Section: Static Inflation V-p Curvementioning
confidence: 99%
“…On this basis it can be concluded that: 1) in five patients the aerated lung units retained nearly normal elastic properties, while in the other seven patients they became stiffer; and 2) airway resistance remained essentially normal in nine patients, increased in two patients, and probably decreased in one patient. Higher than expected values of Est,L could reflect fibrosis [6][7][8][9][10] and/or altered surfactant [33], while the contrasting changes in Rint,L could reflect the interaction of multiple factors (increased lung recoil, release of bronchoconstrictor or bronchodilating agents, intraluminal secretions, peribronchial oedema or infiltrates). That multiple factors with opposite effects were modulating the airway resistance of our patients, besides a reduction in ventilated lung units, is also suggested by the absence of a significant correlation between Est,L and Rint,L ( fig.…”
Section: Elastance and Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Pneumocystis carinii (P. carinii) is associated with histologic findings of interstitial pneumonitis and sometimes irreversible fibrotic changes (2). It has been reported that the severity of HIV-associated PCPis related to the percentage of neutrophilic granulocytes in the bronchoalveolar lavage (BAL) fluid at the time of diagnosis (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary infection with P. carinii is associated with histologic findings of interstitial pneumonitis and irreversible fibrotic changes (3,4). KL-6, a human MUCImucin (5-7), has been reported to be a sensitive serum markerfor interstitial pneumonitis (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%